TRAUMATIC EXPERIENCES AND PSYCHOPATHIC TRAITS IN THE NOVEL HANNIBAL RISING BY THOMAS HARRIS: A PSYCHOLOGICAL STUDY OF THE MAIN CHARACTER - Femy Ramadhina; Agnes Setyowati H; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2020)
This researchs titled is "Traumatic Experiences and Psychopathic Traits in the Novel Hannibal Rising by Thomas Harris: A Psychological Study of The Main Character". This study aims is to show the effect of childhood traumatic memory on the psychopathic traits of the main character using intrinsic and extrinsic approach. This study also uses descriptive analysis methods and library research technique. The main character in this novel is Hannibal, he is a medical student who experiences post-traumatic stress disorder which is the result of the death of his sister. This resulted in Hannibal having psychopathic traits. His psychopathic trait has both negative and positive side. The negative side is effected by his aunt and led him to some of the  murder cases that killed the criminals who killed his sister. The positive side however, despite his psychopathic traits and improper actions, he manage to achieve success in his career which indicates his remarkable accomplishment.Keywords : memory; trauma psychopathic traits; psychologica.